Sebuah Review: Evaluasi dan Optimasi Jaringan Perpipaan Air Bersih - Dwi Cahya Rada; Radianta Triatmadja; Johan Syafri Mahathir A (Lambung Mangkurat University Press, 2021)
This paper aims to provide a review of the evaluation and optimization of the water pipeline system for the community. This paper consists of two parts, namely the evaluation of the design of the installed transmission pipeline and the optimization of the distribution pipeline design to the public. The method that has been used in previous research is the basis for discussion. Evaluation and optimization methods are discussed using software to get the most suitable method.